Eco-friendly synthesis of carbon nanotubes and their cancer theranostic applications - Mostafavi, Ebrahim; Iravani, Siavash; Varma, Rajender S; Khatami, Mehrdad; Rahbarizadeh, Fatemeh (Materials advances, 2022)
Carbon nanotubes (CNTs) with attractive physicochemical characteristics such as high surface area, mechanical strength, functionality, and electrical/thermal conductivity have been widely studied in different fields of science. However, the preparation of these nanostructures on a large scale is either expensive or sometimes ecologically unfriendly. In this context, plenty of studies have been conducted to discover innovative methods to fabricate CNTs in an eco-friendly and inexpensive manner. CNTs have been synthesized using various natural hydrocarbon precursors, including plant extracts (e.g., tea-tree extract), essential oils (e.g., eucalyptus and sunflower oil), biodiesel, milk, honey, and eggs, among others. Additionally, agricultural bio-wastes have been widely studied for synthesizing CNTs. Researchers should embrace the usage of natural and renewable precursors as well as greener methods to produce various types of CNTs in large quantities with the advantages of cost-effectiveness and environmentally benign features. In addition, multifunctionalized CNTs with improved biocompatibility and targeting features are promising candidates for cancer theranostic applications owing to their attractive optical, chemical, thermal, and electrical properties. This perspective discusses the recent developments in eco-friendly synthesis of CNTs using green chemistry-based techniques, natural renewable resources, and sustainable catalysts, with emphasis on important challenges and future perspectives and highlighting techniques for the functionalization or modification of CNTs. Significant and promising cancer theranostic applications as well as their biocompatibility and cytotoxicity issues are also discussed.